Cardiodepressant Effects of Ethanol Extract of Pomegranate (Punica granatum) Skin on Rat Isolated Heart - N Latifipour; HR Kazerani (Institue of Medicinal Plants, ACECR, 2013)
Background: Pomegranate skin is used in traditional medicine and it posseses potent antioxidant properties. Objective: Thisresearch studied the effects of ethanol (80%) extract of pomegranate skin on isolated heart activity. Methods: Isolated rat hearts (n=8) were perfused using Langendorff technique. Following stabilization for at least 20min, lyophilized extract of pomegranate skin at concentratations equal to 0.1, 0.5 and 1% (5min each, respectviely) were added to the perfusion (Krebs) solution. During the experiment, the heart rate, cardiac contractile force and coronary perfusion pressure (as an indicator for coronary tone) were studied. Results: Upon addition of pomegranate skin extract, the mean heart rate gradually declined, a reduction from 223 beats per min at the beginning to 79 beats per min at the end of treatment course (p<0.001). Left ventricular developed pressure(LVDP) showed a significant reduction following addition of the extract (p<0.001). Coronary perfusion pressure gradually increased and was 23% higher by the end of the treatment (p<0.001). Conclusion: The current research suggests potent cardiodepressant effects for water alcoholic extract of pomegranate skin.